Effects of Censorship Disclaimers in Persian Gulf War Television News on Negative Thought Elaboration - NEWHAGEN, JOHN E. (Communication Research, 1994)
An experiment investigated how viewers process censorship disclaimers in 1991 Persian Gulf war television news stories. Gilbert's two-stage verification model was used to test whether images of death and suffering would affect the assessment of censorship disclaimers. Results supported predictions that the mere presence of a disclaimer increases cognitive load on the viewer, thus reducing thought elaboration about it. Further, when the disclaimer is assessed for its narrative meaning, capacity is increased, and more thought elaboration about the story takes place. Disclaimers at the beginning of stories were more effective in promoting thought elaboration than disclaimers at the end. Results suggest disclaimers may be an effective device in messages that are not complex or cognitively demanding. However, their effects may be neutralized by the kinds of images that populate violent television programming.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8wMDkzNjUwOTQwMjEwMDIwMDU